Il principio del superiore interesse nei servizi specialistici di tutela minorile. La sfida dell’alterità culturale e l’urgenza dell’ascolto - Zecca Castel, Raúl (Antropologia Pubblica, 2024)
This article intends to problematize the concept of well-being as a privileged object of public welfare policies, especially with respect to its declination in the context of social services dedicated to child protection, where it is recognized and pursued in terms of an unspecified "superior interest". Starting from an anthropological perspective, and leveraging a historical-comparative approach, I will propose the deconstruction of these ethnocentric representations, to show their culturally situated nature. Even before that, the deconstruction of the very concept of childhood and "minority" will be proposed, even problematizing the more general concept of family. The goal of this contribution – also thanks to some significant ethnographic testimonies personally collected as part of a research carried out in the framework of the project “Families. Strengthening territorial ties to support vulnerable families" (FAMI 2014-2020) – is to solicit critical reflections in child protection services in order to implement the adoption of more aware and adequate interpretative and operational tools, also in the face of dynamics of cultural essentialization and social stereotyping potentially prejudicial for the fulfillment of the professional mandate to which service operators are called, especially when engaged in activities such as assistance and taking charge of users of foreign origin.